Effects of Dividends on Stock Prices in Nepal - Joshi, Rabindra (NRB Economic Review, 2012)
This paper examines the impact of dividends on stock price in the context of Nepal. A majority of earlier studies conducted in developed countries show that dividend has a strong effect than retained earnings. The study examines whether this is consistent in the context of Nepal (or not) and the implication particularly to the banking and non-banking sector. To achieve the objective of the study, a descriptive and analytical research design has been administered. The secondary data are used to test this impact. In order to examine the impact of dividends on stock prices, a multivariate linear regression analysis has been implied in which current market stock price is taken as a dependent variable and four other variables namely Dividend Per Share (DPS), Retained Earnings Per Share (REPS), Lagged Price Earnings Ratio (P/E ratio) and Lagged Market Price Per Share (MPS) as the explanatory variables. This attempt has been made to test the dividends retained earning hypothesis and to examine the estimated relationship over the period of time. The overall conclusion drawn in this study reveals that, the impact of dividends is more pronounced than that of retained earnings in the context of Nepal. Dividend has a significant effect on market stock price in both banking and non-banking sector.